Research on the impact of basic psychological needs satisfaction on career adaptability of Chinese college students - Xu, Min; Lu, Haidong; Guo, Qi (Frontiers in Psychology, 2023)
To explore the relationship and mechanism between basic psychological needs satisfaction and career adaptability of college students. Data were collected from 690 students across 6 universities in China. Findings indicated a significant positive correlation between basic psychological needs satisfaction, career decision self-efficacy, career outcome expectations and career adaptability; career decision self-efficacy plays a partial mediating role between college students' basic psychological needs satisfaction and career adaptability; the latter half path of the mediation model was regulated by perceived career outcome expectation, career outcome expectation played a regulatory role in career decision self-efficacy on career adaptability. It was concluded that college students' basic psychological need satisfaction can positively predict career adaptability directly and indirectly affect career adaptability through career decision self-efficacy and that career outcome expectations have a moderating role between career decision self-efficacy and career adaptability.